Marine pipeline–seabed interaction modeling based on Kerr-type foundation. (November 2018) - Antonio, Leonardo Machado; Pavanello, Renato; Barros, Pérsio Leister de Almeida
Abstract: Within the offshore oil and gas industry, the subsea pipelines in riser configuration are the main choice for petroleum transportation till the processing platform. The subsea pipeline is subject to considerable loads ranging from hydrodynamics forces from the sea current to seabed contact forces. Those contact forces are very important in risers design life, since high and concentrated bending moment stresses are observed in the region where the pipeline starts to be supported by the seafloor. The proper representation of the soil behavior in contact with the structure comprises a very important topic of study in subsea pipelines. In this context, a consistent pipeline–seabed interaction model based on Kerr-type foundation is presented. A finite element formulation for the soil, where the stiffness matrix is derived from a variational formulation of a three parameter elastic foundation model, is proposed. The pipeline is modeled as a planar beam undergoing large displacements using a co-rotational approach. The unilateral contact between soil and pipeline is dealt with a step-loading procedure. The proposed model is able to solve problems where the pipeline is initially placed above the foundation surface and subsequent contact with the seafloor is induced by large displacement of the structure. Numerical examples are presented in order to validate the foundation formulation and explore the proposed contact solution between a pipeline and the seabed. A static analysis of a steel catenary riser (SCR) is presented using the proposed soil–structure interaction model.